Online Learning Activities During the Covid-19 Pandemic - Markuna, Markuna (Jurnal Pendidikan Indonesia, 2022)
The impact of the COVID-19 pandemic affects psychological conditions and patterns of human behavior that have a broader nature over a longer time. This also has an impact on the education system in Indonesia. Teachers and students will get used to doing distance learning interactions. The Work from Home policy applies to lecturers/employees and learning from home for students. This study aims to analyze online learning activities during the Covid-19 pandemic in the Tarbiyah Department. This study uses a descriptive method with a qualitative approach with informants consisting of lecturers and students in the Department of Tarbiyah Education. Based on the results of the study, it can be seen that the learning carried out during the Covid-19 pandemic in the education department used an online model with applications in the form of V-class, Meet Unsil, Zoom, WhatsApp, Telegram, Google Classroom, Youtube, Facebook, and Messenger. The implementation of online learning runs smoothly, although it is felt less than ideal. Student learning outcomes vary, ranging from unsatisfactory, moderate to good. Constraints faced by students and lecturers in online learning including the availability of internet quota, unstable network, and supporting tools such as gadgets and laptops. Online learning is considered effective if it is applied during the COVID-19 pandemic, but a more varied model is needed to keep it interesting if used in the long term.